Politicization compared: at national, European, and global levels - Michael Zürn (Journal of European Public Policy, 2019)
The current literature on politicization can be separated into three groups: politicization within national political systems, of the EU, and of international institutions. In spite of speaking about a similar phenomenon based on a common definition, these three strands of literature do not interact with each other and display, beyond the definitional consensus, significant differences. The focus on different political levels also leads to various assessments. This contribution compares these three strands of literature with the goal of showing that it is necessary to simultaneously look at all three levels to understand the dynamics of politicization and de-politicization. There is a significant potential of analyzing different (de-)politicization processes in an integrative framework to provide fresh insights for each of the fields. In fact, some of the differences between the three kinds of literature can be resolved only by looking at the three levels in parallel.
Keywords: 330; politicization; multilevel politics; integration; technocratic governance; cleavage